Optimized complete cytoreduction in ovarian cancer through intraoperative real-time tumor visualization by 5-ALA – a case report - Tascón Padrón, Laura; Egger, Eva K.; Ralser, Damian Johannes; Otten, Lucia; Toksöz, Özer-Altan; Kristiansen, Glen; Stummer, Walter; Mustea, Alexander (Frontiers in Oncology, 2023)
Complete macroscopic cytoreduction represents the most important prognostic parameter for overall survival in ovarian cancer. This dogma remains tenacious despite significant improvements in adjuvant systemic treatment. Hence, optimization of surgical therapy is an overarching goal to improve patients' outcomes. In this context, intraoperative tumorspecific imaging might facilitate optimized cytoreduction. In neurosurgery, intraoperative 5aminolevulinic acid (5-ALA) guided imaging is applied in clinical routine to assess surgical resection margins. Here, we report the case of a patient with ovarian cancer in whom intraoperative 5-ALA tumor visualization led to optimized complete cytoreduction.Intraoperative administration of 5-ALA led to improved complete cytoreduction by identification and resection of additional ovarian cancer tumor manifestations.The 39-year-old patient, Jehovah`s witness, presented to our department with a left sided ovarian mass, suspicious of ovarian cancer, based on clinical examination, sonographic suspicious features and a CA12-5 elevation. The patient's medical history and family history was unremarkable. Preoperative CT imaging of the thorax and abdomen showed no pathology besides the adnexal mass. Surgery was performed by a midline laparotomy with hysterectomy, bilateral adnexectomy, pelvic peritonectomy, omentectomy, ureterolysis, diaphragm stripping, adhesiolysis and the collection of peritoneal and rectal samples. Intraoperative 5-ALA imaging using a dedicated excitation and detection loupe system (Reveal, DVI) led to tumor detection at the diaphragm, the omentum and the rectum that was not detectable by palpation and visualization using white light. The pathology results revealed that the 5-ALA positive samples (diaphragm, rectum and omentum) obtained by intraoperative 5-ALA were positive for ovarian cancer.Intraoperative administration of 5-ALA represents a promising approach to improve complete cytoreduction in ovarian cancer surgery thereby improving clinical outcomes. Hence, further research and clinical trials are required to investigate the potential of intraoperative 5-ALA imaging in ovarian cancer debulking surgery and its impact on longterm clinical outcomes.